Sustainable water generation: grand challenges in continuous atmospheric water harvesting. Issue 8 (30th June 2022) - Poredoš, Primož; Shan, He; Wang, Chenxi; Deng, Fangfang; Wang, Ruzhu
Abstract : This perspective provides possible development paths for future advancement of continuously operated sorption and radiative sky cooling atmospheric water harvesting on material and system levels. Abstract : Sorption- and radiative sky cooling-based atmospheric water harvesting (AWH) technologies hold promise to provide decentralized fresh water in highly remote and arid regions. The recent emergence of advanced energy materials such as hygroscopic metal–organic frameworks, hydrogels and nanoporous composite sorbents, in addition to radiative sky cooling materials provided the necessary means for AWH. However, truly continuously operational devices are yet to be developed and field-tested. The research focus is now facing a paradigm shift, as future AWH systems are challenged to provide water generation on a kilogram scale, finally meeting a recommended daily water intake per person. This criterion can be adeptly met with continuously operated devices in comparison to discontinuous ones, providing much needed compactness alongside energy and mass efficiency. Here we critically discuss the drawbacks of current energy materials as well as system designs that hinder the use of continuous AWH. Based on identified challenges we outline viable scientific and technological paths. In addition, a possible synergistic effect of sorbents and radiative sky cooling materials on material and system levels to achieve 24 hour continuous fresh water generation is discussed. The provided development paths can spur voluminous avenues into sustainable continuous AWH exploration, making the ultimate goal "to provide fresh water for all" a step closer.